Effects of feeding corn Stover silage treated with optigen or soybean meal on digestibility, rumen fermentation, blood biochemistry and growth performance of fattening lambs - Abu El-Hamed, MA; Mohsen, MK; Abdel-Raouf, EM; Gaafar, HM; Hassan, NIM (Journal of the Hellenic Veterinary Medical Society, 2024)
Eighteen male Rahmani lambs with 4 months old and weighed 25.47±0.17 kg live body weight were divided into three identical groups. In the first group, the lambs were fed on R1, which contained 60% concentrate feed mixture (CFM) and 40% corn stover silage (CSS) and considered as a control. Whereas, lambs in the second group were fed (R2) 50% CFM and 50% CSS supplemented with 0.5% Optigen® (slow-release urea) and the third group fed (R3) 50% CFM and 50% CSS supplemented with 3% soybean meal. Results indicated that the dry matter (DM) and crude protein (CP) contents increased with soybean meal supplement, but nitrogen free extract (NFE) content in silage tended to decrease with Optigen and soybean meal supplementation. Content of DM reduced in R2 with optigen supplementation. Higher CF, NDF, ADF and ADL contents and lower NFE content in R2 and R3 than those of R1content and lower NFE content in R2 and R3 than R1. The R2 and R3 had substantially higher digestion of all nutrients (OM, DM, CP, CF, NFE, and ether extract (EE)) as well feeding values (DCP and TDN) than R1. Lambs in various groups had almost equal ruminal pH values. Concentrations of ammonia-N and total VFA’s in rumen fluid were significantly higher (P<0.05) in R2 and R3 compared to R1. Blood plasma biochemical profiles of the various groups were almost identical, with only minor variations. Intake of DM and CP were slightly higher in R2 and R3 than those of R1. The TDN and DCP intake were significantly (P<0.05) higher in R2 and R3 than R1. The final live body weight, total weight gain, and average daily gain (ADG) were significantly greater (P<0.05) in R2 and R3 than those of R1. DM and CP conversion improved significantly in R2 and R3 than R1. The addition of corn stover silage supplemented with 3% soybean meal or 0.5 % Optigen was improving feed intake, digestion, feed conversion, rumen function, and body weight gain of growing Rahmani lambs.